2020
DOI: 10.3390/ma13214913
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SiC Reinforcement and Its Variation on the Mechanical Characteristics of AZ91 Composites

Abstract: In this study, the processing of SiC particulate-strengthened magnesium alloy metal matrix composites via vacuum supported inert atmosphere stir casting process is presented. The effects of small variations in the SiC particulate (average size 20 µm) reinforcement in magnesium alloy AZ91 were examined. It was found that with the addition of SiC particulate reinforcement, the hardness improved considerably, while the ultimate tensile and yield strength improved slightly. The density and porosity of the magnesiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 41 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…Magnesium-based alloys are getting attention due to their lightweight capabilities. They also exhibit good castability, weldability, machinability, thermal stability, specific mechanical properties, and resistance to electromagnetic radiations [ 1 , 2 , 3 , 4 , 5 ]. The limitation of magnesium-based materials arises from its low ductility, modulus, and poor corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Magnesium-based alloys are getting attention due to their lightweight capabilities. They also exhibit good castability, weldability, machinability, thermal stability, specific mechanical properties, and resistance to electromagnetic radiations [ 1 , 2 , 3 , 4 , 5 ]. The limitation of magnesium-based materials arises from its low ductility, modulus, and poor corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The metal matrix composites of AZ91 magnesium alloy with different types of ceramics and metallic reinforcements were fabricated. Their physical, mechanical properties were evaluated by various researchers [ 2 , 4 , 6 , 7 ] to know the effect of the addition of different reinforcements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whenever there is grain refinement, by applying the load, dislocation reaches the grain boundary; since atoms on the other side are oriented slightly, larger stress is required by dislocation to change its coarseness. This increases the strength of the material [ 27 ]. The ultimate tensile strength of the material increases by 6.8%, 11.4%, and 18.8% for 3%, 6%, and 9% ZrB 2 composite, respectively, as compared to pure ADC12, as shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The articles included in the Special Issue explore the development of sustainable composites with valorized manufacturability for a breakthrough from conventional practices and corresponding to the Industrial Revolution 4.0 ideology. The publications revealed that the application of nano-particles improves the mechanical performance of composite materials [ 6 ]; advanced woven fabrics efficiently reinforce soft body-armor [ 7 ]; heat-resistant aluminum composites ensure the safety of overhead power transmission lines [ 8 ]; chemical additives can help in detecting temperature impact on concrete structures [ 9 ]. The publications [ 10 , 11 ] investigated connection problems of high-performance composites.…”
mentioning
confidence: 99%